Environmental Leadership and Employees' Organizational Citizenship Behavior Towards the Environment (OCBE): Psychological Distance as a Moderating Variable - Soon-Yew, Ju; Noor Azlinna, Azizan; Ramayah, Thurasamy (2015)
Global warming and climate change has become a rigorous worldwide topic that poses many dangers to the environment and human systems (Robertson & Barling, 2013) which eventually affect human health (McMichael, Woodruff & Hales, 2006; Patz et al., 2005). Worse still, it impacts heavily on low-income countries (Haines et al., 2006) and developing countries (Hoegh-Guldberg & Bruno, 2010). Population and urbanization has been identified as the main factors contributing to global warming and climate change. Population on the earth is not likely to stop growing and is expected to increase to 9.6 billion in year 2050 to 10.9 billion in year 2100 (Gerland et al., 2014), and most of the increase in population occur in the continent of Africa and Asia. Without doubt Malaysia too has experienced continues growth in population. According to Malaysia's Statistics Department, the Malaysian population has tripled since 1963 and reached 30 million on February 2014 (The Star, February 26, 2014). The crucial increase of population in Malaysia and rapid process of urbanization places a great challenge to Malaysia’s government agencies in terms of service delivery processes (Mutalib, 2013) one of the major service deliveries concerns is environmental waste disposal.